Correlates of longevity - Fahed-Sreih, Josiane (2008)
This study tests various hypotheses concerning the relationship between correlates of effective succession planning and longevity, using a sample of Lebanese family firms. The findings lend support to the hypotheses regarding how proper succession planning and healthy family relationships positively affect the longevity of the firm and thus the success of the firm. However, the model used does not lend support to the hypothesis that openness and liberal attitudes to accepting qualified successors, whether from within or from outside the firm, is positively correlated with longevity. In fact, the findings suggest a negative relationship between liberal attitudes and longevity, suggesting that older businesses have more conservative attitudes than younger businesses towards family members and outsiders in the family firm